Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 4 - Section 4.2 - Solving Systems of Linear Equations by Substitution - Exercise Set: 11

Answer

x = -2 y = 4

Work Step by Step

x + 2y = 6 2x + 3y = 8 To the first equation x + 2y - 2y = 6 - 2y x = 6 - 2y Substitude x for 6 - 2y to the second equation 2 ( 6 - 2y ) + 3y = 8 12 - 4y + 3y = 8 use the distributive property 12 - y = 8 simplify 12 - y - 12 = 8 - 12 minus 12 to both sides - y = - 4 y = 4 Substitude y for 4 to the first equation x + 2 $\times4$ = 6 x + 8 = 6 x + 8 - 8 = 6 - 8 minus 8 to both sides x = -2
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.